STRATEGI PEMASARAN PRODUK UMRAH PADA TRAVEL SMARTS UMRAH LAMPUNG - Nur Syamsiyah (Multazam : Jurnal Manajemen Haji dan Umrah, 2023)
This study uses the theory put forward by Kotler and Keller regarding the marketing mix, which is divided into the 7 Ps (product, promotion, price, place, people, process, and physical evidence), to discuss the marketing strategy for Umrah products at Travel Smart Umrah Lampung. This study aims to reveal the marketing strategy used by Travel Smarts Umrah to increase the number of pilgrims. This research is qualitative descriptive research, or field research, which uses primary and secondary data sources. The methods used to collect data are observation, interviews, and documentation. Based on the research conducted, Travel Smarts Umrah Lampung's marketing strategy to increase the number of pilgrims uses two methods: placing advertisements on all social media, going directly to prospective pilgrims, and distributing flyers through official Travel Smarts Umrah partners. In addition, through the ta'lim assembly, partnering with agencies, offering a bailout payment system, and prioritizing services for pilgrims.